NURTURING TOLERANCE IN PRESCHOOLERS BY TRANSCARPATHIA CHILDREN’S LITERATURE (LATE 20th – EARLY 21st CENTURIES) - Reho, Hanna (Mountain School of Ukrainian Carpaty, 2025)
The changes in Ukraine place higher demands on the human community, and on new forms of coexistence in today's society. There is a need to nurture tolerant relationships that contribute to the free development of each member of society, the formation of soft skills, thanks to which communication between people becomes balanced and open. Already from preschool age, it is important to teach a child to live in peace and tolerance for different people, beliefs, and viewpoints, the ability to defend their rights and freedoms without violating the rights and freedoms of others, readiness for constructive interaction and mutual understanding with people, regardless of their views and behavior as the basis of civilized relations. The purpose of this publication was to conduct a study of possible methods and means of nurturing tolerance in preschoolers using the literary works of Transcarpathian writers in the studied period. The following theoretical research methods have been used: analysis, comparison, systematization and generalization of data based on the study of psychological and pedagogical, scientific literature and fiction. Having analyzed the literature, we came to the conclusion that a person's life among other people is a contradictory and dynamic process that requires each individual to learn the realities of social and individual existence, the norms and rules of spiritual and material coexistence in accordance with their own capabilities, beliefs and level of culture. Folklore and writings of Transcarpathian writers and poets contribute to the formation of these norms and rules. By listening to fairy tales, stories and poems, the child gets to know the world around them, the people who care about them, etc. Therefore, the child learns to understand the inner world of the heroes, and through them - the inner world of other people, learns to sympathize with them, to believe in the forces of good, to gain self-confidence. The use of the thematic richness of fairy tales, poems, short stories, and small folklore genres significantly affects the formation of tolerance in preschoolers, affects their behavior and actions. Listening to a literary work gives the child the opportunity to imagine themselves in the place of the characters, to expand the spectrum of their own thoughts and feelings, contributes to a better understanding of themselves and others, and allows them to change their viewpoint in relation to the emotional states of their peers. Children's literature in Transcarpathia was and is one of the key links of spiritual life. Oleksandr Havrosh, Yuliia Drahun, Stepan Zhupanyn, Halyna Malyk, Lidiia Povkh, Volodymyr Fedynyshynets, Yurii Shyp, Vasyl Shkiria and others have been fruitfully working here. Analyzing the writings of poets and writers for children and about children, we can say that the literature of Transcarpathia in late 20th - early the 21st centuries is full of ideas for educating the younger generation in the spirit of tolerance, high moral qualities, and friendly relations based on mutual assistance, trust, friendly and open communication.